Band gap-tuned MoS2(1−x)Te2x thin films synthesized by a hybrid Co-sputtering and post-deposition tellurization annealing process. Issue 16 (10th August 2017) - Hibino, Yusuke; Ishihara, Seiya; Sawamoto, Naomi; Ohashi, Takumi; Matsuura, Kentarou; Machida, Hideaki; Wakabayashi, Hitoshi; Ogura, Atsushi
Abstract: Abstract : MoS2(1− x ) Te2 x thin films were fabricated by high-temperature co-sputtering deposition and post-deposition tellurization annealing using novel Te precursor ( i -C3 H7 )2 Te for the first time. As a result, high crystal quality MoS2(1− x ) Te2 x (6.5 nm) were successfully fabricated with the Te concentration x ranging from 0.48 to 0.61 and band gap value from 0.80 to 0.87 eV. From the obtained band gap values of MoS2(1− x ) Te2 x, the bowing parameter b was determined to be 1.06 eV. When exploited in device use, if the required band gap value is known, the required composition can be calculated with the bowing parameter. We have also shown the compatibility of co-sputtering to alloy fabrication since the composition ratio can be easily controlled just by adjusting the radio frequency (RF) sputter power on different targets. The fabrication method can be applied to different transition metal dichalcogenide materials as well.